Management accounting practices: a case of Jordanian manufacturing companies / Shamsi S. Bawaneh. - S. Bawaneh, Shamsi (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
The study aims to report the importance and current use of management accounting practices in textbooks and the broader literature. Data was generated using a questionnaire, which was conducted on a sample of 30 manufacturing companies in Jordan. Descriptive statistics on the usage of individual practices provide the basis for discussion. The results showed that the respondents perceived Management Accounting Practices (MAPs) to obtain relevant information for proper decision making. Several factors, including nature of the business, type of information needed for making decisions, and utilization of existing resources, affect the choice of MAPs used by the manufacturing companies. The study has shown that MAPs supported the organizational structure and management accounting processes. Management accounting can provide relevant information for capital investment decisions, which allow accountants to produce discounted cash flow, payback period, and accounting rate of return.